Variations in Lateral Sphenoid Sinus Wall Defects - Nakache, Gabriel; Yakirevitch, Arkadi; Bedrin, Lev (Indian Journal of Neurosurgery, 2015)
Objective The article aims to present different forms of lateral sphenoid sinus wall defects.Study Design Case series and literature review.Methods A comparison between two patients who presented with spontaneous CSF rhinorrhea, defects in the lateral wall of the sphenoid sinus, and meningeal contents in the sphenoid sinus based on MRI is discussed. Both patients were operated endoscopically, through a trans-nasal-ethmoid-pterygoid approach.Results In the first patient, a meningoencephalocele, protruding through a defect in the lateral sphenoid sinus wall and pterygoid base, occupied the inferior part of the sphenoid sinus. In the second patient, there were no exposed meningeal contents inside the sphenoid sinus. Instead, the lateral sphenoid sinus wall was thin and bulging medially into the inferior part of the sinus, with the dura and temporal lobe covered with thin bony cap.Conclusion Complete dehiscence of the lateral wall of the sphenoid sinus results in exposed meningeal contents inside the sphenoid sinus. In partial dehiscence, the thin and weakened lateral wall of the sphenoid sinus yields to the pressure of the temporal lobe and bulges into the sphenoid sinus cavity. There are no other descriptions of partially dehiscent lateral sphenoid sinus walls in the literature.
Keywords: sphenoid sinus; lateral wall defect; meningoencephalocele